The Psychometric Properties of the Original Version of Assessment of Time Management Skills (ATMS). (3rd February 2022) - Roshanay, Afsaneh; Janeslätt, Gunnel; Lidström-Holmqvist, Kajsa; White, Suzanne; Holmefur, Marie
Abstract : Background . To perform daily activities, time management and organizational skills are essential and therefore also important intervention focus in occupational therapy. To guide and evaluate intervention, valid and reliable instruments that measure time management and organization skills are necessary. The aim of this study was to evaluate the psychometric properties of the Assessment of Time Management Skills (ATMS). Methods . Eligible participants were volunteer adults from the general population who were aged between 18 and 65 years, had a good understanding of English, and were not currently involved in any training or education to improve time management. The ATMS was filled out as a computer-administered survey. Rasch measurement analysis was used to evaluate the validity and aspects of reliability of the ATMS. Results . In total, 241 adults (112 male and 129 female, mean age = 40 ) participated. The analysis of principal components of residuals (PCA) and the item goodness-of-fit indicated that the 30-item scale does not measure only one single trait. Three subscales, time management (11 items), organization and planning (11 items), and regulation of emotion (5 items), were detected. One item each on the 11-item subscale showed misfit, but they were kept due to high relevance. All three subscales showed excellent results on analyses of PCA, local independence, and reliability. Conclusions and Relevance . ATMS can provide valid measures of time management, organization and planning skills, and regulation of emotion in a general population and presumably also in a population with cognitive impairment. The measure is useful for occupational therapists in assessing patients' strengths and barriers in time management skills. It can also be useful in identifying the necessity of training time management skills, to guide OT intervention programs and to evaluate interventions. What This Article Adds . Knowledge about the psychometric properties and usefulness of the ATMS in English-speaking countries.